Become who you are : with an additional essay "The old woman" - Dohm, Hedwig, 1833-1919 (SUNY series, women writers in translation., 2006)
"Hedwig Dohm (1831-1919) was a thinker and writer significantly ahead of her time. She championed women's rights in Germany and criticized with acerbic wit the social, political, and familial inequities inherent in gender relationships at the time of the first wave of the women's movement. Her novella Become Who You Are is about a woman, Agnes Schmidt, whose husband has died and who is grappling with finding an identity for herself as an aging widow - reflecting the restrictions imposed especially on aging, widowed women who often yearn for a life and identity of their own. Also included here is the English translation of Dohm's essay, "The Old Woman," which is a compelling call for women to resist the social, intellectual, psychological, and physical restraints placed on women of Dohm's time."--BOOK JACKET.